Pengaruh Stres Kerja dan Kepuasan Kerja terhadap Kinerja Pegawai pada Dinas Pekerjaan Umum Kota Sungai Penuh - Mauledy Ahmad (Journal on Education, 2022)
This study aims to determine : 1) The extent to which the influence of the Work Stress To The Employee Performance In Department Of Public Works Sungai Penuh City, 2) The extent to which the influence of the Job Satisfaction To The Employee Performance In Department Of Public Works Sungai Penuh City, 3) The extent to which the influence of the Work Stress and Job Satisfaction To The Employee Performance In Department Of Public Works Sungai Penuh City. Because in this study the number of employees who worked in the Department Of Public Works Sungai Penuh City were 45 people, so in the sampling in this study was a population study of 45 people. Based on the results of the study showed that : Work Stress negative and not significant effect on Employee Performance In Department Of Public Works Sungai Penuh City, Job Satisfaction positive and significant effect on Employee Performance In Department Of Public Works Sungai Penuh City, Work Stress And Job Satisfaction positive and significant effect on Employee Performance In Department Of Public Works Sungai Penuh City.